Ақпараттық технологияларды қолдану - интербелсенді оқытуға ықпал етуші жол - Шолпанбаева, Г.А.; Ловцова, Д. П. (My University, 2016)
The necessity of examining the information and computer tecnologies as pedagogical programming support in Kazakh language teaching in higher educational institution is observed in this article.
Keywords: information technologies; electronic textbook; multimedia system; Interactive education; module educatin; intellectual; potential